Fumonisin B1 inhibits apoptosis in HepG2 cells by inducing Birc-8/ILP-2. Issue 2 (1st June 2015) - Chuturgoon, Anil A.; Phulukdaree, Alisa; Moodley, Devapregasan
Highlights Fumonisin B1 (FB1) inhibits apoptosis in HepG2 liver cells. FB1 significantly up-regulated the anti-apoptotic Birc-8/ILP-2 gene and protein expression. FB1 significantly decreased phosphorylated γH2AX and cleaved PARP in HepG2 cells. FB1 decreased expression of Smac/DIABLO. FB1 modulates apoptosis in a complex dose dependent regulation of pro-and anti-apoptotic molecules.